Assessing cybersecurity vulnerabilities in the disposal of ewaste in South African public & private institutions - Khumalo, Dimitri (University of the Witwatersrand, Johannesburg, 2022)
Over the years there have been numerous studies conducted, focusing on the various facets of waste electronic and electrical equipment, also termed electronic waste or e-waste, and the impact it has on the environment. However, little attention has been placed on the management of personal data during the disposal phases of e-waste and the inherent ramifications it poses if this data were retrieved. This study sought to assess the vulnerabilities to which organisations are exposed, specifically financial and government institutions, by interrogating the management policies, processes, and procedures for stored data when disposing of e-waste at the end of the asset life cycle. A qualitative research method, through semi-structured interviews was conducted. The population selected were very senior individuals, selected based on the specific roles and experiences they fulfilled within the financial services sector, various government institutions, and e-waste recycling companies. From the findings, it emerged that there were growing concerns around the effective policy regulations put in place to manage the disposal practices of ewaste and that of personal identifiable and sensitive data of individuals. This has driven a need for policies and robust mechanisms to be instituted to try and minimise the overall impact these vulnerabilities could pose to the environment and the entire value chain, at that juncture where electronic devices have reached their EOL and are now being disposed of. iii The results demonstrate that more focus has to be placed on the managing of ewaste in industry, providing policy directives in relation to how organisations need to prescribe and conform to effective disposal practices of electronic devices that have reached their EOL. Further to this, government, in consultation with various industry role players, needs to look at ways to formalise and regulate the e-waste sector and institute measures to ensure conformance for every part of the value chain.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law and Management, University of the Witwatersrand, 2022
Keywords: Cybersecurity; Electronic Waste (e-waste); E-waste Policies; Financial Service; Hazardous waste; Waste Electric and Electronic Equipment (WEEE); SDG-15: Life on land